Improving Personal Letter Writing Skills Through Outlining Technique: A Quasi-Experimental Study at State Islamic Senior High School - Elvira Nazarina; Rofiqoh Rofiqoh; Sukmawati Sadilia; Andi Patmasari (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2026)
This study was conducted to prove that the use of outlining can improve the personal letter writing skills of eleventh grade students of State Islamic Senior High School. Despite the recognition of outlining as an effective pre-writing strategy, few researchers have examined the effectiveness of the strategy as a tool for teaching personal letter writing among secondary students. Personal letter writing is unique compared to other forms of writing in that students are expected to arrange their ideas systematically but also express their personal experience, emotions, and interpersonal relations effectively in the process. Thus, the present study was designed to measure the effectiveness of the outlining strategy in enhancing personal letter writing skills among students. This study utilized a quantitative research design where 43 participants were assigned into two groups; experimental group composed of 21 students and control group comprised of 22 students. In the experimental group, the outlining strategy was used as a tool while the conventional method was used among the control group students. It was noted that there was an increase in the mean score of the experimental group from 62.43 during the pre-test to 86.67 during the post-test, while the control group recorded scores of 66.77 during the pre-test and 76.09 during the post-test. In addition, the results from the independent-samples t-test suggested that there was a statistically significant difference between the two groups (t= 6.282, p< .001). Lastly, from the effect size analysis, the effect size value was found to be Cohen’s d = 1.92, which indicates a large effect. Therefore, this shows that outlining is an effective instructional method for enhancing students’ personal letter writing abilities. This study has established that English teachers should apply outlining as a useful instructional strategy to enable their students to write good personal letters. Moreover, this study has added to the existing body of knowledge on writing theory by proving empirically that outlining is an effective strategy for planning purposes.